Technologie informatyczne wykorzystywane w controllingu - Chomiak-Orsa, Iwona (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The aim of this article is to present the essence and the importance of controlling information system. The paper also discusses categories of the software applications which supports a controlling system in an organization. To manage the controlling processes effectively, managers need to analyze data collected from different sources and transform them. In this respect information technology generates a lot of solutions. One of them is Business Intelligence which is more and more often used in a lot of enterprises. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 44-52